Efficient Tandem Addition/Cyclization for Access to 2,4-Diarylquinazolines via Catalytic Carbopalladation of Nitriles - Julin Gong; Kun Hu; Yetong Zhang; Yinlin Shao; Tianxing Cheng; Maolin Hu; Jiuxi Chen (Molecules, 2019)
The first example of the palladium-catalyzed tandem addition/cyclization of 2-(benzylidenamino)benzonitriles with arylboronic acids has been developed. This transformation features good functional group tolerance and provides an alternative synthetic pathway to access 2,4-diarylquinazolines in moderate to good yields. A plausible mechanism for the formation of 2,4-diarylquinazolines involving sequential nucleophilic addition followed by an intramolecular cyclization is proposed.